2016
DOI: 10.21117/rbol.v3i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Análise Dos Perfis De Clínicas Odontológicas E De Cirurgiões-Dentistas Em Duas Redes Sociais Quanto Aos Aspectos Éticos, De Propaganda E Publicidade

Abstract: Introdução: O Brasil é o país com o maior número de cirurgiões-dentistas do mundo e, devido à má distribuição deste grande número de profissionais, existe uma grande concorrência entre eles, gerando uma necessidade para o profissional de lançar mão de ferramentas que possam ajudar na busca e manutenção de clientes. Objetivo: Avaliar duas redes sociais (Facebook® e Instagram®) de cirurgiõesdentistas e clínicas odontológicas em relação aos cumprimentos dos preceitos do Código de Ética Odontológica (CEO), bem com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 4 publications
0
15
0
6
Order By: Relevance
“…Digital marketing, a type of external marketing, is an effective and simple option, from which the professional has the right to dispose, provided in an ethical way [6,7].…”
Section: Digital Marketingmentioning
confidence: 99%
See 4 more Smart Citations
“…Digital marketing, a type of external marketing, is an effective and simple option, from which the professional has the right to dispose, provided in an ethical way [6,7].…”
Section: Digital Marketingmentioning
confidence: 99%
“…In a study conducted by Serra et al [4], it was found that only 61 professionals from a total sample of 975 used it, however, recent research has found an increasing number of pages (websites and social networks) used as a dental marketing tool [6,7,22] .…”
Section: Digital Marketingmentioning
confidence: 99%
See 3 more Smart Citations